2018
DOI: 10.2139/ssrn.3278425
|View full text |Cite
|
Sign up to set email alerts
|

Health Shocks and the Evolution of Consumption and Income over the Life-Cycle

Abstract: This paper studies the effects of health on earnings dynamics and on consumption inequality over the life-cycle. We build and calibrate a life-cycle model with idiosyncratic health, earnings and survival risk where individuals make labor supply and asset accumulation decisions, adding two novel features. First, we model health as a complex multi-dimensional concept. We differentiate between functional health and underlying health risk, temporary vs. persistent health shocks, and predictable vs. unpredictable s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 78 publications
0
15
0
Order By: Relevance
“…Consider a model with a 100% job offer 38 While a decline in health does not reduce wages immediately, it will reduce wages over time through its effect on accumulated work experience. This mechanism was found to be important by Capatina, Keane, and Maruyama (2018). 39 Both future and present marriage market opportunities matter for schooling decisions.…”
Section: Identificationmentioning
confidence: 94%
See 1 more Smart Citation
“…Consider a model with a 100% job offer 38 While a decline in health does not reduce wages immediately, it will reduce wages over time through its effect on accumulated work experience. This mechanism was found to be important by Capatina, Keane, and Maruyama (2018). 39 Both future and present marriage market opportunities matter for schooling decisions.…”
Section: Identificationmentioning
confidence: 94%
“…This mechanism was found to be important by Capatina, Keane, and Maruyama (2018). Consider a model with a 100% job offer 38 While a decline in health does not reduce wages immediately, it will reduce wages over time through its effect on accumulated work experience.…”
Section: Identificationmentioning
confidence: 99%
“…In fact, the vast majority of life cycle models that account for health consider only a single health index (see French, 2005;French and Jones, 2011;French et al, 2018;Braun et al, 2015;De Nardi et al, 2017;Pashchenko and Porapakkarm, 2013;Aizawa and Fu, 2017, as well as the references in Footnote 24. Exceptions include Capatina et al, 2018, andGustman andSteinmeier, 2014). However, we found that the most commonly used measure of health in structural studies, which assesses whether the respondent has a health condition that limits work, understates the impact of health on labor employment modestly in the HRS and strongly in ELSA relative to our preferred measure.…”
Section: Using the Reduced Form Regressions To Assess Structural Models Of Healthmentioning
confidence: 91%
“…5 Modeling a higher variance of shocks after some event (here birth) can be found in the macro-health literature. For example, in Capatina, Keane, and Maruyama (2017), the variance of income increases after a bad health shock which shifts health from a good to a bad state/regime.…”
Section: Theorymentioning
confidence: 99%